Desenvolvimento de website para uma marca de cachaça artesanal regional do Paraná - Melo, Pamela Campos de (2018)
The project has as problem the request of a company that produces artisinal products in the coast of Paraná and needs to improve its information channel in the internet with its clients. As a solution was proposed the production of a website for the brand of artisan cachaças Xirú do Sambaqui. In order to meet this demand, it was necessary to base web usability, responsive design, Search Engine Optimization (SEO), as well as seeking knowledge about photography, color, typography and production of web content. The project methodology was based on Duckett (2011), through questioning project requirements with client and potential users, market research, development of sitemap, content and wireframe for desktop and mobile; getting to the production of layout, code programming, testing and SEO. As a result, it was developed the design project and programmed a website with the use of languages such as HTML, CSS, Javascript and libraries such as Bootstrap. With web good practices and a real domain that is online, this website has been through responsiveness and usability testing with real users. The results of the tests were positive, as we were able to develop a website that meets the web's responsiveness and usability requirements, allowing it to be opened on computers, cell phones or tablets. For SEO, the technical part has been designed so that within time that takes for searching engines to consider relevant new content, the website may be among the first results of it such as Google. The development of this work allowed the application of Graphic Design knowledge integrated to the knowledge of Web Design and programming in a real application.